Why patients visit dentists – A study in all WHO regions - John, Mike T. (J Evid Based Dent Pract, 2020)
BACKGROUND: The dimensions of oral health-related quality of life (OHRQoL) Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact are the major areas where patients are impacted by oral diseases and dental interventions. AIM: The aim of this study was to evaluate whether dental patients’ reasons to visit the dentist fit the four OHRQoL dimensions. METHODS: Dentists (N=1,580) from 32 countries participated in a web-based survey. For their patients with current oral health problems, dentists were asked whether these problems were related to teeth, mouth, and jaws’ function, pain, appearance, or psychosocial impact or whether they do not fit into the previous four categories. Dentists were also asked about their patients who intended to prevent future oral health problems. For both patient groups, the proportions of oral health problems falling into the four OHRQoL dimensions were calculated. RESULTS: For 96 out of 100 dental patients, their current oral health problems were related to teeth, mouth, and jaws’ function, pain, appearance, or psychosocial impact. For 92 out of 100 dental patients, the oral health problems they intended to prevent in the future were related to the OHRQoL dimensions. Both numbers increased to 98% or higher when experts analyzed dentists’ explanations of why some oral health problems would not fit these four categories. None of the dentist-provided explanations suggested evidence against the OHRQoL dimensions as the concepts that capture dental patients’ suffering. CONCLUSION: Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact capture dental patients’ oral health problems worldwide. These four OHRQoL dimensions offer a psychometrically sound and practical framework for patient care and research, identifying what is important to dental patients.